Anatomical Variants of Foramen Ovale and Foramen Spinosum. - Hema, Lattupalli; Kumari, Makani Tanuja; Rao, Madala Venkateswara (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Foramen ovale and spinosum are important foramina of the greater wing of the sphenoid. Normal variations in their shapes and sizes are quite common and widely studied. Aim and Objectives: To conduct a morphometric study of foramen ovale and spinosum of the human sphenoid bone. Material and Methods: The present study was conducted over 100 dry human skulls obtained from Anatomy department, Narayana Medical College, Nellore, and Andhra Pradesh. In this study presence of anatomic variations in shape of foramen ovale and Spinosum was noted and length and width of foramen were measured. Various shapes of these two foramina were also noted and photographed. Comparison between right and left was done. Results: Mean length of foramen ovale was 5mm on the right side and 5.05mm on the left side and mean width was 3.75mm on the right side and 2.65 mm on the left side. There was no significant difference between mean of the length and width of the right and left foramen ovale. Foramen ovale was typically oval in 119 sides, almond in 12 sides, round in 55 sides and slit like in 2.There was presence of fusion of foramen ovale and spinosum in one case. In case of foramen spinosum mean length on the right side is 2.25 mm and on the left side is 2.1respectively. Mean width on the right side is 3.55 mm and on the left side is 1.75 mm. foramen spinosum was round in 105 sides, oval in 23 sides, pin hole in 32 sides and irregular in 40 sides. Conclusion: Anatomical variations in size and shape of foramen ovale could be explained according to its development. Hence, considering the surgical and diagnostic importance of foramen ovale and spinosum, this study would be added to the literature for the future generations.